CURAHAN WAKTU KERJA PETANI PADI DENGAN POLA NAFKAH GANDA SEBAGAI PENCARI GURITA DI DESA LINAU KECAMATAN MAJE KABUPATEN KAUR - fariadi, herri; Andriani, Evi; Al-Hakim, Muhammad Farid (Lampung University, 2025)
The high potential for Octopus production in Kaur Regency encourages rice farmers to implement a double income pattern strategy. The aim of this research is to determine the number of hours rice farmers work as octopus hunters, and to analyze the variables that influence the working hours of rice farmers with a double income pattern in Linau Village, Maje District, Kaur Regency. A total of 36 rice farmers who carried out a dual income pattern as octopus hunters became respondents in this research. The census method was used for sampling. This research was carried out from March to April 2023. The method used to determine the number of working hours of rice farmers as octopus searchers used descriptive analysis and analyzed the factors that influence the working hours of rice farmers with a double income pattern as Octopus searchers in Maje District, Kaur Regency. The results of the research show that the time that rice farmers in Linau Village, Maje District, Kaur Regency devote to working in farming is an average of 4 hours per day or 131 hours per month, and to work outside of farming is an average of 5 hours per day or 153 hours per month. The results of the study show that income as an octopus seeker (X1), income from rice farming (X2), and number of dependents (X5) affect the amount of working hours of rice farmers, while the variables of age (X3), formal education (X4) and work experience (X6) do not affect the amount of working hours of rice farmers. Keywords: double income pattern, octopus seeker, outpouring of working time